The deceivers Allied military deception in the Second World War - Holt, Thaddeus (Skyhorse Publishing, 2007)
Secret Codes, ciphers, strategic misdirection, and more: Deception was one of the most powerful weapons utilized by the Allies in World War II. Here are all the amazing tricks and leaked misfortunes—many revealed for the first time—that helped lure the Axis powers into false, even dangerous, positions. The collection of incredible codes, surreptitious spies, and false battle plans is made all the more enjoyable by Thaddeus Holt’s masterful writing, as well as the accompanying photos. His novel-like storytelling includes many illuminating profiles of the war’s central figures and the roles they played in specific deceptive operations.